Digital Transformation of Primary Education in Saudi Arabian Schools: Trends and Impacts - Abdallah Al-Shreifeen, Iyad (Lafadz Jaya Publisher, 2023)
The digitalization of education has become an essential component of the modern educational system, particularly in Saudi Arabia, where the government has invested significantly in technological advancement within its schools. This study aims to analyze the ongoing digitalization efforts in primary education in Saudi Arabia, focusing on the trends, impacts, and effectiveness of technology on teaching and learning processes. By reviewing current policies, analyzing the integration of digital tools in classrooms, and examining the experiences of teachers and students, this article presents a comprehensive understanding of how digital education is being implemented in the Kingdom. The study also explores the implications of digital tools on student engagement, learning outcomes, and overall educational quality. The findings suggest that while progress has been made, further investment in professional development and infrastructure is crucial to ensure the sustainability of digital education in primary schools. The paper concludes with recommendations for policy development and strategic planning to enhance the digitalization of education in Saudi Arabia.